Marine natural products. Issue 2 (6th February 2020) - Carroll, Anthony R.; Copp, Brent R.; Davis, Rohan A.; Keyzers, Robert A.; Prinsep, Michèle R.
Abstract : A comprehensive review of 1554 new MNPs, including numerous novel and bioactive compounds from marine bacteria. Abstract : This review covers the literature published between January and December in 2018 for marine natural products (MNPs), with 717 citations (706 for the period January to December 2018) referring to compounds isolated from marine microorganisms and phytoplankton, green, brown and red algae, sponges, cnidarians, bryozoans, molluscs, tunicates, echinoderms, mangroves and other intertidal plants and microorganisms. The emphasis is on new compounds (1554 in 469 papers for 2018), together with the relevant biological activities, source organisms and country of origin. Reviews, biosynthetic studies, first syntheses, and syntheses that led to the revision of structures or stereochemistries, have been included. The proportion of MNPs assigned absolute configuration over the last decade is also surveyed.